Extending the Technology Acceptance Model to Explain How Perceived Augmented Reality Affects Consumers' Perceptions - Oyman, Mine; Bal, Dondu; Ozer, Serhat (Pergamon-Elsevier Science Ltd, 2022)
Today, reaching consumers through interactive methods has become one of the primary goals of the brands. As a result of this, smartphones have turned into tools brands can use to start an interaction with consumers. Due to augmented reality (AR)-supported mobile applications, brands can both provide consumers with detailed information about products and services, and also affect consumers' perceptions. The main purpose of this research is to determine the effect of augmented reality use in mobile applications on consumers' behavioral intentions towards the use of the mobile application and perceptions underlying this effect. In this study, by employing the Technology Acceptance Model (TAM), the effect of augmented reality on behavioral intentions for mobile application use was examined through a structural equation modeling (SEM). Additionally, the effects of the technology anxiety (TA) and consumer novelty seeking (CNS) on perceived augmented reality were also examined. An augmented reality-supported mobile application which makes trying cosmetic products virtually on possible, was used by female consumers (n = 278). The data was collected through a questionnaire. The results indicated that the CNS had a positive and direct effect on perceived augmented reality (PAR); PAR had a positive and direct effect on perceived enjoyment (PE), perceived usefulness (PU), perceived informativeness (PI), and perceived ease of use (PEU). It was also determined that the PE, PU, PI had positive and direct effects on the behavioral intentions to use the application (BIUA).
Ozer, Serhat/0000-0001-7626-6487;
Keywords: Augmented Reality; Ar-Supported Mobile Applications; Consumer Novelty Seeking; Consumer Perceptions; Usage Intention; Technology Acceptance